Case Report: A good response to furmonertinib second-line treatment of an advanced lung adenocarcinoma patient with a rare EGFR exon 20 N771_P772insH mutation: A case report and literature review - Zhang, Xiao; Han, Huan; Zhao, Jiuzhou; Liu, Xiao; Zhang, Jianbo; Sun, Rui; Li, Shaomei; Liu, Baoxing; Zhu, Hui; Jiao, Shuyue; Li, Xiang; Tang, Hong (Frontiers in Pharmacology, 2022)
Background: Lung adenocarcinoma with the classical EGFR 19 deletion and exon 21 L858R point mutations has exhibited good responses to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) treatment. However, the sensitivity of uncommon EGFR exon 20 insertion mutation to third-generation EGFR-TKIs has not been determined. Although emerging targeted therapies for EGFR exon 20 insertion mutation have been reported in recent years, such patients still have a poorer prognosis than those with typical or wild-type EGFR mutations. Case summary: Here, we report the case of a 57-year-old man with advanced non-small cell lung cancer (NSCLC) with a rare EGFR exon 20 N771_P772insH mutation. The patient was treated with furmonertinib as second-line therapy. Although his pleural effusion was more than before that during treatment, various examination results showed that the pleural effusion was closely related to hypoproteinemia; thus, local progression was not considered. His cough was significantly alleviated, and the dose was well tolerated. The patient was evaluated for a remarkable progression-free survival (PFS) of 10.0 months, a duration of response (DOR) of 8.0 months, and an overall survival (OS) of 22.0 months, which had not previously been achieved. Conclusion: The present study indicated that furmonertinib might be a good treatment option for first-line progressive NSCLC patients with EGFR exon 20 insertion mutation.